1999
DOI: 10.1063/1.124963
|View full text |Cite
|
Sign up to set email alerts
|

Room-temperature 1.3 μm emission from InAs quantum dots grown by metal organic chemical vapor deposition

Abstract: Articles you may be interested inComplete suppression of large InAs island formation on GaAs by metal organic chemical vapor deposition with periodic As H 3 interruption Appl. Phys. Lett. 90, 033105 (2007); 10.1063/1.2432285 Charged exciton emission at 1.3 μ m from single InAs quantum dots grown by metalorganic chemical vapor deposition Appl. Photopumped red-emitting InP/In 0.5 Al 0.3 Ga 0.2 P self-assembled quantum dot heterostructure lasers grown by metalorganic chemical vapor deposition Appl. Phys. Lett. 78… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 11 publications
1
19
0
Order By: Relevance
“…Ground-state lasing at RT, high internal quantum efficiency, and low threshold current density have already been demonstrated in both stacked-layer [2]- [5] and single-layer QD lasers [6], [7]. Efficient [8] and narrow-linewidth [9] RT emission at 1.3-m wavelength has been achieved recently, and the first QD lasers operating in this wavelength region are already reported [10]- [13]. Other properties, like differential gain, small signal modulation bandwidth, and alpha parameter, are still under discussion in the comparison between the expected superior performances and the measured values.…”
Section: Introductionmentioning
confidence: 99%
“…Ground-state lasing at RT, high internal quantum efficiency, and low threshold current density have already been demonstrated in both stacked-layer [2]- [5] and single-layer QD lasers [6], [7]. Efficient [8] and narrow-linewidth [9] RT emission at 1.3-m wavelength has been achieved recently, and the first QD lasers operating in this wavelength region are already reported [10]- [13]. Other properties, like differential gain, small signal modulation bandwidth, and alpha parameter, are still under discussion in the comparison between the expected superior performances and the measured values.…”
Section: Introductionmentioning
confidence: 99%
“…Only a few works have shown luminescence and electroluminescence at 1.3 m in QDs fabricated by MOCVD. [5][6][7] A variety of theoretical 8 and experimental 9 studies have recently reported the existence of a permanent electron-hole dipole moment in a QD, which is related to the built-in strain field inside the dots. The permanent dipole is sensitive to the detailed structure of the dots, which is strictly related to the growth conditions.…”
mentioning
confidence: 99%
“…10 Very few works report emission wavelength near 1.3 m in binary QDs fabricated by metal organic chemical vapor deposition ͑MOCVD͒. 11 In this letter, we target the optimization and the tuning of the emission wavelength of InGaAs QDs grown by MOCVD in the strategic wavelength range of 1.3 m. The QD structures solely based on InGaAs/GaAs, optimized for device applications ͑i.e., with high density, narrow size dispersion, and efficient room temperature emission͒ can be tuned only up to 1.29 m without reaching the exact value of 1.3 m. Instead, by inserting the same QD structure ͑fabricated with the same MOCVD growth parameters͒ into an In x Ga (1Ϫx) As layer, the emission wavelength can be extended up to 1.39 m.…”
mentioning
confidence: 99%